2007
DOI: 10.1172/jci31570
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of integrin α4β7 suppresses lymphocyte migration to the gut

Abstract: Integrin adhesion molecules mediate lymphocyte migration and homing to normal and inflamed tissues. While the ligand-binding activity of integrins is known to be modulated by conformational changes, little is known about how the appropriate balance of integrin adhesiveness is maintained in order to optimize the migratory capacity of lymphocytes in vivo. In this study we examined the regulation of the gut homing receptor α 4 β 7 integrin by manipulating at the germline level an integrin regulatory domain known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 54 publications
5
60
1
Order By: Relevance
“…In agreement with this hypothesis, our flow cytometric and biotinylation analyses showed that S3-5 mutant cells highly expressed the active form of ␣5␤1 on the cell surface. Similarly, Park et al previously reported that aberrant activation of integrin ␣4␤7 suppressed lymphocyte migration and underscored the importance of a proper balance in the adhesion and de-adhesion of integrin (34). The enhanced expression of active ␤1 on the cell surface might have been due to different trafficking events, since the internalization of the active form of ␣5␤1 but not the total version was significantly delayed in S3-5 cells compared with that in WT cells.…”
Section: Discussionmentioning
confidence: 75%
“…In agreement with this hypothesis, our flow cytometric and biotinylation analyses showed that S3-5 mutant cells highly expressed the active form of ␣5␤1 on the cell surface. Similarly, Park et al previously reported that aberrant activation of integrin ␣4␤7 suppressed lymphocyte migration and underscored the importance of a proper balance in the adhesion and de-adhesion of integrin (34). The enhanced expression of active ␤1 on the cell surface might have been due to different trafficking events, since the internalization of the active form of ␣5␤1 but not the total version was significantly delayed in S3-5 cells compared with that in WT cells.…”
Section: Discussionmentioning
confidence: 75%
“…Integrins must be regulated to be activated and deactivated quickly in mammalian cells, even within seconds. It has been shown that detachment of integrin from ligands in the trailing edge is critical for integrin functions (46), and mutations that constitutively active integrins result in malfunctions (47)(48)(49)(50). Therefore, it is unlikely that integrin TM domains form more stable homomeric association during inside-out signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the a 4 b 7 integrin was further evaluated through the manipulation of an integrin regulatory domain (adjacent to metal iondependent adhesion site [ADMIDAS]), a domain that normally serves to raise the activation threshold of a 4 b 7 and stabilize it in the nonadhesive state [Park et al 2007]. Lymphocytes from mice harboring a disrupted ADMIDAS expressed an a 4 b 7 integrin that persistently adhered to MAdCAM-1 and also exhibited improper de-adhesion.…”
Section: Approaches To Targeting Adhesion Molecules and Their Associamentioning
confidence: 99%